Novel platensimycin derivatives with herbicidal activity - Moraes, Fernanda C; Alvarenga, Elson S; Amorim, Kariny B; Demuner, Antonio J; Pereira‐Flores, Milton E (Pest Management Science, 2015)
Faced with the need to develop herbicides with different modes of action on account of weed resistance to existing herbicides, the sesquiterpene lactones can be the starting point in the search for new bioactive compounds. Lumisantonin and five novel amides have been evaluated against two monocotyledons and three dicotyledons. An efficient and versatile synthesis of lumisantonin and the five novel amides has been accomplished from readily available α‐santonin. These compounds were subjected to evaluation for their biological activity against Sorghum bicolor (sorghum), Allium cepa(onion), Cucumis sativus (cucumber), Solanum lycopersicum (tomato) and Bidens pilosa(beggartick). Lumisantonin has inhibited the development of the aerial parts of sorghum and onion by 76 and 67% at 1000 µM respectively. One of the novel amides has prevented the growth of shoots and radicles of sorghum by 80 and 71% at 1000 µM respectively.All of the tested compounds have been found to exhibit promising seed germination inhibition. We can conclude that lumisantonin was on average the most lethal against all plant species evaluated; however, two of the novel amides have exhibited inhibition selectivity against monocotyledons when compared with dicotyledons.
Keywords: Herbicide; Amide; Lumisantonin; Platensimycin; Sorghum; Onion; Beggartick; Cucumber